Sato – Beckmann classification of accounting for technological progress: genesis, generalisation, and extension - Khatskevich, Guennadi A.; Pranevich, Andrei F. (Journal of the Belarusian State University. Economics, 2021)
In this paper, we consider inverse problems of identifying dynamic aggregated production functions from given conditions of neutrality of technological progress. Sets of production functions with Hicks neutral technological progress, Harrod neutral technological progress, and Solow neutral technological progress are described. The Sato – Beckmann classification of neutrality of technological progress for linear-homogeneous production functions is given. The Sato – Beckmann classification is generalised for general case of dynamic production function. Also, we supplemented the Sato – Beckmann classification with new conditions of neutrality of technological progress and obtained the corresponding forms of dynamic production functions. Using dependencies between three economic and mathematical characteristics of dynamic production function (elasticity of output with respect to capital, elasticity of output with respect to labour, and the factor proportions, the output-capital ratio, the output-labour ratio, the average product of generalised factor), we obtain new cases of neutrality of technological progress. By statistical data for 1990–2018, we built the dynamic production function with Hicks neutral technological progress for modeling the economic growth of the Republic of Belarus.